The NeMo real-time fMRI neurofeedback study: protocol of a randomised controlled clinical intervention trial in the neural foundations of mother-infant bonding - Eckstein, Monika; Zietlow, Anna-Lena; Gerchen, Martin Fungisai; Schmitgen, Mike; Ashcroft-Jones, Sarah; Kirsch, Peter; Ditzen, Beate (BMJ open, 2019)
Introduction: Most mothers feel an immediate, strong emotional bond with their newborn. On a neurobiological level, this is accompanied with the activation of the brain reward systems, including the striatum. However, approximately 10% of all mothers report difficulties to bond emotionally with their infant and display impaired reward responses to the interaction with their infant which might have long-term negative effects for the child’s development. As previous studies suggest that activation of the striatal reward system can be regulated through functional MRI (fMRI)-based neurofeedback (NFB), we have designed and investigate fMRI-NFB training to treat maternal bonding difficulties. - Methods and analysis: In the planned trial, mothers will be presented pictures of their infant and real-time fMRI (rtfMRI), peripheral measures, neural, endocrine, psychophysiological and behavioural measures will be assessed. Mothers with bonding difficulties (n=68) will be randomised to one of two double-blind intervention groups at 4-6 months postpartum. They will participate in three repeated NFB training sessions with rtfMRI-NFB training to increase activation of (a) the ventral striatum or (b) the anterior cingulate. Interview data and real-time mother-infant interaction behaviour pre-intervention, post-intervention and at follow-up will serve as clinical outcome measures. - Ethics and dissemination: Study procedures are in line with the recommendations of the World Medical Association (revised Declaration of Helsinki) and were approved by the Ethics Committee of the Medical Faculty, s-450/2017, Heidelberg University. All participants will provide written informed consent after receiving a detailed oral and written explanation of all procedures and can withdraw their consent at any time without negative consequence. Results will be internationally published and disseminated, to further the discussion on non-pharmacological treatment options in complex mental disorders. - Trial registration number DRKS00014570; Pre-results.
Gesehen am 11.10.2019